Effect of Alpha-lipoic Acid and Vitamin E in Diet on the Performance, Antioxidation and Immune Response in Broiler Chicken - Srilatha, T.; Reddy, V. Ravinder; Qudratullah, S.; Raju, M.V.L.N. (International Journal of Poultry Science, 2010)
An experiment was conducted to study the effects of alpha-lipoic acid at graded levels (0, 20, 40, 60, 80 mg/kg), Vit-E (10, 50 mg/kg) and their combination in a 5 x 2 factorial design on performance, anti-oxidation and immune response of broilers. 400 day-old male broilers were divided into 10 treatment groups, each with 8 replications (5 broilers in each) and fed one of the test diets till 6 weeks of age. Supplementation of Lipoic acid in broiler diet at 80 mg/kg gave significantly (p